Mapping out factors that undermining vaccine uptake in Malaysia: a multiple perspective - Yusoh, Mohd Helmi; Wan Mohd Ghazali, Wan Norshira; Abdul Manan, Kamaruzzaman; Mohamed, Shafizan; Mohd Nasir, Nur Shakira; Mohamad, Saifullah; Idris, Hamidah (Kulliyyah of Medicine, International Islamic University Malaysia, 2024)
INTRODUCTION: Malaysia has recorded a sporadic increase in vaccine-preventable diseases in many different states such as Johor, Perak, Selangor, and Sabah, to name a few. What is more worrying was the drastic drop in vaccination for children especially the measles, mumps, and rubella (MMR) vaccination during the early period of COVID-19 pandemic in 2020. On this basis, this paper is intended to interrogate why vaccine uptake has decreased over the years. When vaccination became a global concern with the surge of COVID-19 cases in the first quarter of 2020, further questions were posed to understand the reality behind vaccine rejections and refusals. MATERIALS AND METHODS:This study employs a focus group discussion and in-depth interviews to explore the vaccine refusal phenomenon in Malaysia. Theoretical sampling led to the recruitment of participants from health institution, media organisation, and vaccine refusal individuals as they are useful to provide different yet connected insights into the phenomenon under study. RESULTS:Under the constructivist-interpretivist paradigm, grounded theory revealed that micro and macro factors jointly contribute to vaccination refusals. CONCLUSIONS:Considering these factors, this study suggests the importance of health literacy and synergised policies to protect, educate, and guide society on vaccine-related matters